Seven new species of Chimarra (Trichoptera: Philopotamidae) from Malawi - Wahlberg, Emma; Espeland, Marianne; Johanson, Kjell Arne (Zootaxa, 2014)
For the first time species of caddisflies in the genus Chimarra Stephens 1829 are reported from Malawi. The following new species are described: Chimarra zombaensis, C. flaviseta, C. chichewa, C. circumverta, C. mulanjae, C. psittacus and C. calidopectoris. The descriptions add to the knowledge of Afrotropical diversity in the order Trichoptera.